El matrimonio nace... el Dos posiciones de cara matrimonio muere... al fracaso conyugal (Estudio Agustiniano, 2012)
This reflection on “Marriage is born... marriage dies” arose from a confrontation between the vision of Benedict XVI and an Italian newspaper(II Corriere della Sera) with respect to marriage. The catholic church has traditionally been part of the indissolubility of marriage. While the civil law, in general, look at the possibility of divorce. In attempting to resolve the conflict today, now are some alternatives that look at the possibility or reconciling the right with pastoral care, especially as regards the indissolubility of marriage.